Online higher education during the pandemic: The case of Hungary - Dunajeva, Jekatyerina (Przegląd Krytyczny, 2022)
The coronavirus pandemic has profoundly affected Hungarian higher education (HEI). As campuses around the globe were forced to shut down, online distance learning became an everyday reality for all students. At the same time, faculty were rushed to adjust their teaching content and methods, as well as forms of assessment, to online teaching. As a result, this transition exposed flaws in technological abilities, digital preparedness and flexibilities within universities. In this work, my goal is to analyze how the Hungarian HEIs adopted online educational practices during the pandemic and how they were able to address some of the difficulties while adjusting their teaching and creating new forms of support for both students and faculty. To that end, the article first discusses the prevalence of distance and digital learning before the pandemic, then evaluates the steps and challenges of transition to remote online education during the pandemic, and finally highlights some lessons learnt and best practices of some Hungarian universities.